Biomechanical properties of articular cartilage in different regions and sites of the knee joint: acquisition of osteochondral allografts - Yongsheng Ma; Qitai Lin; Xueding Wang; Yang Liu; Xiangyang Yu; Zhiyuan Ren; Yuanyu Zhang; Li Guo; Xiaogang Wu; Xiangyu Zhang; Pengcui Li; Wangping Duan; et al. (Cell and Tissue Banking, 2024)
Osteochondral allograft (OCA) transplantation involves grafting of natural hyaline cartilage and supporting subchondral bone into the cartilage defect area to restore its biomechanical and tissue structure. However, differences in biomechanical properties and donor-host matching may impair the integration of articular cartilage (AC). This study analyzed the biomechanical properties of the AC in different regions of different sites of the knee joint and provided a novel approach to OCA transplantation. Intact stifle joints from skeletally mature pigs were collected from a local abattoir less than 8 h after slaughter. OCAs were collected from different regions of the joints. The patella and the tibial plateau were divided into medial and lateral regions, while the trochlea and femoral condyle were divided into six regions. The OCAs were analyzed and compared for Young’s modulus, the compressive modulus, and cartilage thickness. Young’s modulus, cartilage thickness, and compressive modulus of OCA were significantly different in different regions of the joints. A negative correlation was observed between Young's modulus and the proportion of the subchondral bone (r = − 0.4241, P < 0.0001). Cartilage thickness was positively correlated with Young’s modulus (r = 0.4473, P < 0.0001) and the compressive modulus (r = 0.3678, P < 0.0001). During OCA transplantation, OCAs should be transplanted in the same regions, or at the closest possible regions to maintain consistency of the biomechanical properties and cartilage thickness of the donor and recipient, to ensure smooth integration with the surrounding tissue. A 7 mm depth achieved a higher Young's modulus, and may represent the ideal length.

Variability in the phytoplankton response to upwelling across an iron limitation mosaic within the California current system - YuanYu Lin; Olivia Torano; Logan Whitehouse; Emily Pierce; Claire P. Till; Matthew Hurst; Robert Freiberger; Travis Mellett; Maria T. Maldonado; Jian Guo; Mariam Sutton; David Zeitz; et al. (Limnology and Oceanography, 2024)
Coastal upwelling currents such as the California Current System (CCS) comprise some of the most productive biological systems on the planet. Diatoms dominate these upwelling events in part due to their rapid response to nutrient entrainment. In this region, they may also be limited by the micronutrient iron (Fe), an important trace element primarily involved in photosynthesis and nitrogen assimilation. The mechanisms behind how diatoms physiologically acclimate to the different stages of the upwelling conveyor belt cycle remain largely uncharacterized. Here, we explore their physiological and metatranscriptomic response to the upwelling cycle with respect to the Fe limitation mosaic that exists in the CCS. Subsurface, natural plankton assemblages that would potentially seed surface blooms were examined over wide and narrow shelf regions. The initial biomass and physiological state of the phytoplankton community had a large impact on the overall response to simulated upwelling. Following on‐deck incubations under varying Fe physiological states, our results suggest that diatoms quickly dominated the blooms by “frontloading” nitrogen assimilation genes prior to upwelling. However, diatoms subjected to induced Fe limitation exhibited reductions in carbon and nitrogen uptake and decreasing biomass accumulation. Simultaneously, they exhibited a distinct gene expression response which included increased expression of Fe‐starvation induced proteins and decreased expression of nitrogen assimilation and photosynthesis genes. These findings may have significant implications for upwelling events in future oceans, where changes in ocean conditions are projected to amplify the gradient of Fe limitation in coastal upwelling regions.

Pyroptosis in inflammation-related respiratory disease - Yuanyu Feng; Min Li; Xiaoting Yangzhong; Xifeng Zhang; Anju Zu; Yunjiao Hou; Lin Li; Shibo Sun (Journal of Physiology and Biochemistry, 2022)
Pyroptosis is commonly induced by the gasdermin (GSDM) family and is accompanied by the release of inflammatory cytokines such as IL-1β and IL-18. Recently, increasing evidence suggests that pyroptosis plays a role in respiratory diseases. This review aimed to summarize the roles and mechanisms of pyroptosis in inflammation-related respiratory diseases. There are several pathways involved in pyroptosis, such as the canonical inflammasome-induced pathway, non-canonical inflammasome-induced pathway, caspase-1/3/6/7/GSDMB pathway, caspase-8/GSDMC pathway, caspase-8/GSDMD pathway, and caspase-3/GSEME pathway. Pyroptosis may be involved in asthma, chronic obstructive pulmonary disease (COPD), lung cancer, acute lung injury (ALI), silicosis, pulmonary hypertension (PH), and tuberculosis (TB), in which the NLRP3 inflammasome-induced pathway is mostly highlighted. Pyroptosis contributes to the deterioration of asthma, COPD, ALI, silicosis, and PH. In addition, pyroptosis has dual effects on lung cancer and TB. Additionally, whether pyroptosis participates in cystic fibrosis (CF) and sarcoidosis or not is largely unknown, though the activation of NLRP3 inflammasome is found in CF and sarcoidosis. In conclusion, pyroptosis may play a role in inflammation-related respiratory diseases, providing new therapeutic targets.

Precipitable water and CAPE dependence of rainfall intensities in China - Wenhao Dong; Yanluan Lin; Jonathon S. Wright; Yuanyu Xie; Xungang Yin; Jianping Guo (Climate Dynamics, 2019)